ANALISIS PENGARUH MOTIVASI BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Mirna Mirna; Mudjiran Mudjiran; Rohadatul Aysi; Dewi Murni (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Understanding the concept is one of the fundamental goals in learning mathematics. This study aims to determine the effect of learning motivation on students' understanding of mathematical concepts in class XI MIPA at a public high school in Pariaman. The method in this research is descriptive qualitative. Sampling was done by simple random sampling technique. The research instruments used were motivational questionnaires and tests of understanding mathematical concepts that have been tested valid and reliable. The results of the study, learning motivation is in the medium and high categories, affecting the level of understanding of students' mathematical concepts.